2014
DOI: 10.1021/nn503779d
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte Membrane Is an Alternative Coating to Polyethylene Glycol for Prolonging the Circulation Lifetime of Gold Nanocages for Photothermal Therapy

Abstract: Gold nanocages (AuNCs), which have tunable near-infrared (NIR) absorption and intrinsically high photothermal conversion efficiency, have been actively investigated as photothermal conversion agents for photothermal therapy (PTT). The short blood circulation lifetime of AuNCs, however, limits their tumor uptake and thus in vivo applications. Here we show that such a limitation can be overcome by cloaking AuNCs with red blood cell (RBC) membranes, a natural stealth coating. The fusion of RBC membranes over AuNC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
303
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 394 publications
(310 citation statements)
references
References 59 publications
6
303
0
1
Order By: Relevance
“…[18][19][20] The use of natural cellular membranes to camouflage synthetic polymeric nanoparticles has demonstrated significant potential. [21][22][23][24][25] In this study, the membranes of human cytotoxic T lymphocytes (hCTLs) were chosen to produce cancer-targeting nanoparticles, because of the long blood circulation time and the ability to recruit and localize at tumor sites, of this cell type. 22 Leukocytes have a variety of proteins on their membranes to detect inflammation and diseased tissues.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] The use of natural cellular membranes to camouflage synthetic polymeric nanoparticles has demonstrated significant potential. [21][22][23][24][25] In this study, the membranes of human cytotoxic T lymphocytes (hCTLs) were chosen to produce cancer-targeting nanoparticles, because of the long blood circulation time and the ability to recruit and localize at tumor sites, of this cell type. 22 Leukocytes have a variety of proteins on their membranes to detect inflammation and diseased tissues.…”
Section: Introductionmentioning
confidence: 99%
“…150,154,174,175 As an alternative stealth coating material, the membrane of these cells completely covers the NP surface with their "selfmarkers" (ie, proteins, glycans, and acidic sialyl moieties), and the resultant NPs, recognized as the host's own cells, can actively evade the immune system. For example, Piao et al 160 reported that the RBC-coated gold nanocages exhibited longer blood retention compared with the PEGylated counterparts. In addition, the fusion of RBC membranes over gold surface did not alter the unique porous and hollow structures of gold nanocages.…”
mentioning
confidence: 99%
“…Based on a two-compartment model, the RBCNPs possessed a significantly longer systemic circulation than PEGylated PLGA nanoparticles, the elimination half time of RBCNPs was 39.6 h and that of PEGylated nanoparticles was only 15.8 h [28]. A similar result was provided by the comparison between gold nanocages (AuNCs) and RBC membrane coated AuNCs (RBC-AuNCs) [32]. The RBC-AuNCs possessed a nearly ten-fold in vivo circulation lifetime than the poly(vinylpyrrolidone)-coated AuNCs.…”
Section: The Prolonging Systemic Circulation Of Cell Membrane-coated mentioning
confidence: 54%